Temperature‐Dependent Dynamic Strain Aging in Selective Laser Melted 316L. Issue 10 (24th June 2021) - Diepold, Benedikt; Neumeier, Steffen; Meermeier, Annalena; Höppel, Heinz Werner; Sebald, Torsten; Göken, Mathias
Abstract : Additively manufactured austenitic stainless steel AISI 316L (EN 1.4404, X2CrNiMo17‐12‐2) is used at higher temperatures, e.g., in space applications. However, the high‐temperature properties of such materials have not been analyzed in detail yet. Thus, selective laser melted (SLM) 316L is tested in the solution‐annealed condition by compression and tensile tests at temperatures between 25 and 877 °C. The compressive strength of SLM 316L is higher in comparison with the conventionally produced reference material due to hardening by a high dislocation density and a fine substructure. However, tensile tests reveal a loss in ductility of the SLM material at temperatures between 300 and 627 °C, where the elongation to fracture is reduced from 65% to 39%. Alloying elements cause serrated yielding in the affected temperature range. Together with an increased normalized work‐hardening rate and a negative strain rate sensitivity, dynamic strain aging is found to cause the reduction of ductility. Abstract : The deformation behavior of an additively manufactured 316L steel from 25 °C up to 877 °C in comparison with a conventionally produced 316L reference material is investigated. Both reveal serrations in stress–strain curves, higher work‐hardening rates, negative strain rate sensitivities, and a reduction in ductility in the temperature range of dynamic strain.